2020
DOI: 10.1038/s41598-020-74332-1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and site-directed mutagenesis of circular bacteriocin plantacyclin B21AG reveals cationic and aromatic residues important for antimicrobial activity

Abstract: Plantacyclin B21AG is a circular bacteriocin produced by Lactiplantibacillus plantarum B21 which displays antimicrobial activity against various Gram-positive bacteria including foodborne pathogens, Listeria monocytogenes and Clostridium perfringens. It is a 58-amino acid cyclised antimicrobial peptide, with the N and C termini covalently linked together. The circular peptide backbone contributes to remarkable stability, conferring partial proteolytic resistance and structural integrity under a wide temperatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 90 publications
(180 reference statements)
1
13
0
Order By: Relevance
“…Moreover, L. lactis , unlike E. faecalis , is a commonly chosen model organism ( Kunji et al, 2003 ) in both laboratory research and industrial applications for various reasons such as easy manipulation and well-known safety. Based on our constructed expression systems, mutagenesis studies using the two-plasmid system (Cir-A + ΔA) proved to be quite efficient and successful, although various challenges have been reported previously at different stages for heterologous production of circular bacteriocins, such as the difficulty of obtaining positive clones ( Kemperman et al, 2003a ; Gor et al, 2020 ) at the molecular cloning level, and the difficulty in achieving antimicrobial production from hosts of different genera at the peptide expression level ( Fernández et al, 2007 ; Kawai et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, L. lactis , unlike E. faecalis , is a commonly chosen model organism ( Kunji et al, 2003 ) in both laboratory research and industrial applications for various reasons such as easy manipulation and well-known safety. Based on our constructed expression systems, mutagenesis studies using the two-plasmid system (Cir-A + ΔA) proved to be quite efficient and successful, although various challenges have been reported previously at different stages for heterologous production of circular bacteriocins, such as the difficulty of obtaining positive clones ( Kemperman et al, 2003a ; Gor et al, 2020 ) at the molecular cloning level, and the difficulty in achieving antimicrobial production from hosts of different genera at the peptide expression level ( Fernández et al, 2007 ; Kawai et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cationic and aromatic residues are highly conserved among putative and experimentally confirmed circular bacteriocins ( Vezina et al, 2020 ), and have been demonstrated to play important roles in antimicrobial activity of plantacyclin B21AG ( Gor et al, 2020 ). In terms of the mechanism of the antibacterial activity, it has been reported previously that the aromatic residues (such as Trp) have a specific affinity for the region close to the lipid carbonyl and promote membrane permeation, while the cationic residues (such as Lys) have the affinity to the negative charged lipid phosphate region and are believed to interact with negatively charged cell membrane ( Braun and von Heijne, 1999 ; de Planque et al, 1999 ; Killian and von Heijne, 2000 ; Jiménez et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N-terminal regions of circular bacteriocins carry several aromatic and/or hydrophobic amino acids suggesting that these residues play a key role in the biosynthesis and probably the antimicrobial activity [96]. Recently, a structural alignment study of different circular bacteriocins revealed the involvement of charged and aromatic conserved amino acids in antimicrobial activity [104]. Indeed, the authors showed that the substitution of phenylalanine and tryptophan residues by alanine by site-directed mutagenesis of the bacteriocin plantacyclin B21AG produced by Lactiplantibacillus plantarum B21 resulted in a strong reduction of the activity compared to the wild type.…”
Section: Mode Of Action Of Circular Bacteriocinsmentioning
confidence: 99%